2022
DOI: 10.1097/bpb.0000000000000975
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of perioperative blood loss in primary posterior hemivertebra resection for pediatric patients with congenital scoliosis

Abstract: Several studies have elucidated the risk factors of intraoperative bleeding. However, the total blood loss (visible and hidden loss) and related risk factors were seldom reported. In this study, we aimed to identify predictors of massive blood loss in posterior hemivertebra resection for pediatric patients. Clinical records were retrospectively reviewed for 108 pediatric patients who underwent primary posterior hemivertebra resection and spinal fusion for congenital scoliosis from June 2017 to June 2019. Intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The literature regarding HBL in congenital scoliosis, surgery is limited. Recently, Liu et al reported that HBL accounted for 41% of total blood loss in their series with 108 paediatric patients undergoing posterolateral hemivertebrectomy and posterior instrumentation [ 26 ]. Their mean total blood loss of 575 ml was also in line with the results of the current study as we observed a mean total blood loss of 648 ml in the hemivertebrectomy patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature regarding HBL in congenital scoliosis, surgery is limited. Recently, Liu et al reported that HBL accounted for 41% of total blood loss in their series with 108 paediatric patients undergoing posterolateral hemivertebrectomy and posterior instrumentation [ 26 ]. Their mean total blood loss of 575 ml was also in line with the results of the current study as we observed a mean total blood loss of 648 ml in the hemivertebrectomy patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several studies have demonstrated that HBL constitutes a significant part of the total postoperative bleeding also in spinal fusion for scoliosis [ 16 , 17 , 22 , 25 ]. Recently, Liu et al reported that HBL accounted for over 40% of total blood loss in posterior hemivertebra resection for congenital scoliosis [ 26 ]. Hemivertebrectomy and posterior VCR are performed by an extracavitatory approach using costotransversectomy and an extra-pleural approach to enable a safe approach around the spine for osteotomy.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent idiopathic scoliosis (AIS) is a common spinal deformity, and posterior instrumentation and fusion is a common method for treating AIS [ 1 ]. However, the operation is complicated and causes massive intraoperative blood loss (650–2,839 mL) [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the operation is complicated and causes massive intraoperative blood loss (650-2,839 mL) [2][3][4].…”
Section: Introductionmentioning
confidence: 99%